Task allocation algorithm for virtual design organisation in agile industrial design. (2017) - Yang, Gangjun; Zhang, Xueliang
Agile industrial design is a kind of modern industrial design method to deal with the rapid change of market demand. From the perspective of the development trend of industrial design, virtual design organisation will be an important form of agile design organisations. Task allocation of organisation members is the primary work of agile industrial design practice, and it will involve many complex factors. Innovation as the core of industrial design determines its agility. Firstly, the characteristics of industrial design in agile environment were analysed in this paper. On the basis of this study, the influencing factors of virtual organisation task allocation were discussed, and the task allocation factors for virtual organisation were summarised into five aspects, namely, difficulty of innovation, interest degree, ability of comprehensive design, emergency degree of design task, and busy degree of design work. Based on these, the paper focused on the definition of the difficulty coefficient of design exploration, and the calculation method of influencing factors and task allocation algorithm were given, and the results were verified by an example.